Relationship between nurses’ cultural competence and observance of ethical codes - Sadeghi, Narges (Nursing ethics, 2022)
BackgroundCultural competence is considered as one of the main skills of nurses enabling them to provide nursing care for those with different cultures. One of the cases related to nurses’ cultural competence is observance of ethical codes, but it has not been investigated sufficiently in studies.AimThis study has been conducted to determine the relationship between nurses’ cultural competence and observance of ethical codes in practice.Research designThis descriptive-correlational study was conducted in 2020. Sampling was done at several stages. The data were collected using questionnaires of demographic information, cultural competence, and observance of ethical codes as self-report. The questionnaires were provided to the subjects by the corresponding researcher and the data were analyzed using Pearson correlation test.Participants and research contextThis study was done with participation of 267 nurses working in four training hospitals located in northwestern Iran and 16 head nurses of selected wards.Ethical considerationsThe study was approved by Human Ethics Committee of Hamadan University of Medical Sciences. Participation was voluntary. Consent was obtained and confidentiality kept.FindingsThe results of Pearson correlation coefficient test showed a positive and statistically significant relationship between cultural competence and observance of ethical codes (r = 0.524, p = 0.001). In addition, cultural competence and observance of ethical codes by most nurses were at a moderate level.ConclusionsThe results of the present study showed a significant relationship between nurses’ cultural competence and observance of ethical codes. Therefore, it can be concluded that by strengthening the level of nurses, the level of observing ethical codes by them can be increased. Cultural competency and observance of ethical codes are important components of nursing care, and their development can improve nursing care delivery to clients through academic training, hidden curriculum and in-service education.